The Effectiveness of Narcotics Crime Investigation by the Narcotics Investigation Unit from the Perspective of the Indonesian Criminal Procedure Code - Syabdha Alamsyah; Sri Astutik; Noenik Soekorimi (International Journal of Law and Society, 2026)
This research examines the effectiveness of narcotics crime investigation by the Narcotics Investigation Unit (Satuan Reserse Narkoba) from the perspective of Indonesia's Criminal Procedure Code (KUHAP) and related legislation. The study also analyzes the juridical-normative obstacles encountered during investigation processes, along with potential solutions under Indonesian positive law. As an extraordinary crime, narcotics offenses require precise and legally sound investigation methods. However, investigative practices often face challenges due to inconsistencies between legal norms and field implementation, limited resources, and the absence of clear regulations on special investigative techniques such as wiretapping and controlled delivery. This normative legal research employs statutory and conceptual approaches, analyzing primary legal materials including Law Number 8 of 1981 (KUHAP), Law Number 35 of 2009 on Narcotics, and various implementing regulations. The findings indicate that narcotics investigations are not yet optimal due to weak technical regulations, disharmonized laws between KUHAP and the Narcotics Law, overlapping authority between the Police and the National Narcotics Agency (BNN), and a lack of protection for whistleblowers and witnesses. The legal gap in regulating special investigation methods creates uncertainty in evidence admissibility. Proposed solutions include regulatory reform through KUHAP revision, improving investigator competence through specialized training, utilizing modern technology, strengthening inter-agency coordination, and enhancing internal and external oversight mechanisms. Legal reform and institutional synergy are essential to enhancing the overall effectiveness of narcotics investigations in Indonesia.